2007
DOI: 10.1016/j.diabres.2006.07.018
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and the risk of developing type 2 diabetes in Aboriginal Australians

Abstract: ObjectiveTo investigate the association between C-reactive protein (CRP) and the risk of developing diabetes in Aboriginal Australians. Research design and methodsHigh sensitivity CRP levels were measured in 620 Aboriginal participants aged 20-74 years free from diabetes at baseline in a remote community in the Northern Territory of Australia. Participants were followed for a median of 11 years to identify newly diagnosed cases of diabetes. Cox proportional hazards models were used to assess the relationship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Consistent with this study, Claes et al (2014) also found that median CRP levels were higher in Indigenous Australian CKD patients than non-Indigenous Australian CKD patients [287]. Secondly, Wang and Hoy used a cohort study design which followed participants for up to 13 years and found a positive and significant association between CRP and risk for type 2 diabetes [44]. The third study by Wang and Hoy conducted in 2010, also found a positive and significant association between CRP and CVD incidence in a prospective cohort following participants for up to 13 years [288].…”
Section: Crp and Ckd In Indigenous Australianssupporting
confidence: 61%
See 4 more Smart Citations
“…Consistent with this study, Claes et al (2014) also found that median CRP levels were higher in Indigenous Australian CKD patients than non-Indigenous Australian CKD patients [287]. Secondly, Wang and Hoy used a cohort study design which followed participants for up to 13 years and found a positive and significant association between CRP and risk for type 2 diabetes [44]. The third study by Wang and Hoy conducted in 2010, also found a positive and significant association between CRP and CVD incidence in a prospective cohort following participants for up to 13 years [288].…”
Section: Crp and Ckd In Indigenous Australianssupporting
confidence: 61%
“…Sixty seven (6%) had an HbA1c greater than or equal to 6.5% (48 mmol/mol), but had no record of diagnosis or management of diabetes, while 158 (13%) participants had a prior diagnosis of diabetes. A further 195 participants were identified as high risk for developing type 2 diabetes using the IEC (International Expert Committee) 6.0% (42 mmol/mol) cut-off and up to 568 (48%) participants by the ADA criteria of 5.7-6.4% (39)(40)(41)(42)(43)(44)(45)(46) mmol/mol). Participants with known diabetes had HbA1c levels at time of screening between 4.9% (30 mmol/mol) and 15.6% (147 mmol/mol).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations